2013
DOI: 10.1002/ijc.28468
|View full text |Cite
|
Sign up to set email alerts
|

A four‐miRNA signature identified from genome‐wide serum miRNA profiling predicts survival in patients with nasopharyngeal carcinoma

Abstract: Recent findings have reported that human serum microRNAs (miRNAs) can be used as prognostic biomarkers in various cancers. We aimed to explore the prognostic value of serum miRNAs in nasopharyngeal carcinoma (NPC) patients. The level of serum miRNA was retrospectively analyzed in 512 NPC patients recruited between January 2001 and December 2006. In the discovery stage, a microarray followed by reverse transcription-quantitative polymerase chain reaction was used to identify differentially altered miRNAs in eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 41 publications
(86 reference statements)
1
73
0
2
Order By: Relevance
“…It inhibits cell cycle progression by repressing Max and ErbB3 expression post-transcriptionally, mediates the effects of the tumor-suppressor p53, and suppresses interferon gene expression by blocking interferon regulatory factor-5 [49][50][51] . MiR-22 has been proposed as a potential serum marker for non-small cell lung cancer [52] , esophageal squamous cell carcinoma [53] , and nasopharyngeal carcinoma [54] . Our experimental strategy in this study focused on using hybridization-based microarray technology as the means to screen thousands of genes simultaneously, but it is also severely limited due to its issues with reproducibility and its tendency to produce a high rate of false positive and false negative results.…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits cell cycle progression by repressing Max and ErbB3 expression post-transcriptionally, mediates the effects of the tumor-suppressor p53, and suppresses interferon gene expression by blocking interferon regulatory factor-5 [49][50][51] . MiR-22 has been proposed as a potential serum marker for non-small cell lung cancer [52] , esophageal squamous cell carcinoma [53] , and nasopharyngeal carcinoma [54] . Our experimental strategy in this study focused on using hybridization-based microarray technology as the means to screen thousands of genes simultaneously, but it is also severely limited due to its issues with reproducibility and its tendency to produce a high rate of false positive and false negative results.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the down-regulation of tumor suppressor gene expression by microRNAs (miRNAs) is increasingly recognized to be an important mechanism of nasopharyngeal tumorigenesis (Li et al, 2014;Ma et al, 2014). miRNAs are endogenous, small non-coding RNA molecules that completely or partially bind to target mRNAs and either block translation or lead to degradation to ultimately inhibit gene expression (Li et al, 2011;Marquitz et al, 2012;Liu et al, 2014). miRNAs serve as essential posttranscriptional regulators that can specifically influence cancer development and progression, with aberrant expression patterns observed in multiple cancer types (Marquitz, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, miR-638 was identified as a potential predictor of early virological response to interferon treatment in patients with chronic hepatitis B (15). In addition, miR-638 was one of the four miRNAs identified through genome-wide serum miRNA profiling that predict the survival rate of patients with nasopharyngeal carcinoma (28). A previous study demonstrated that the downregulation of miR-638 in colorectal cancer predicts poor survival (13).…”
Section: Of Cases ---------------------------------------------------mentioning
confidence: 99%